LANGUAGE EDUCATION IN THE ASPECT OF PREPARING STUDENTS FOR PROFESSIONAL CAREER - Zhaynagul, Beisenova; Meiramova, Saltanat (European Scientific Journal, ESJ, 2013)
Language policy is one of the fundamental aspects of the language situation, which is determined as the system of measures of conscious influence on the development of linguistic processes, distribution of languages in the spheres of social interaction, and representing a part of the political control over the language situation, linguistic conflicts. Nowadays its importance as a part of a national policy, especially in the multinational Republic of Kazakhstan, is growing more, and consequently, it is becoming more regulating. The main motive power of the language policy in Kazakhstan is its socio-political and legislative activity. Today the State educational standard is the basis of common conceptual language education in Kazakhstan, and it is designed to provide the legal framework for the state cultural project "Trinity of languages". The process of multilingual education in the Humanities universities of Kazakhstan is considered. Special attention is given to the methodological assumption of the educational process of teaching university students Kazakh, Russian, English Languages.